(untitled) (Indian Journal of Public Health Research & Development, 2021)
Ovarian cancer is the third type of gynecologic cancer in terms of prevalence after cervical and uterine cancer. The disease is known as the silent killer as it is slowly spread without a diagnosis, which leads to the worst prognosis and high mortality rate. Libya shows low disease incidence while the high mortality rate is seen in developed countries due to a lack of proper diagnostic and treatment options. This research aims to understand the various risk factors of ovarian cancer described in literature. Based on the literature review related to various factors which are the demographic, reproductive history, hormonal factors, genetic factors, lifestyle such as diet and BMI. Various controversial in literature exist on the effect of these factors and their association with risk factors.